Screening of Neonatal UK Dried Blood Spots Using a Duplex SMN1 Screening Assay - Stuart P. Adams; Emma Gravett; Natalie Kent; Susanne Kricke; Adeboye Ifederu; Mariacristina Scoto; Salma Samsuddin; Francesco Muntoni (MDPI AG, 2021)
Spinal muscular atrophy (SMA) is an autosomal inherited neuromuscular genetic disease caused, in 95% of cases, by homozygous deletions involving the SMN1 gene exon 7. It remains the leading cause of death in children under 2 years of age. New treatments have been developed and adopted for use in many countries, including the UK. Success of these treatments depends on early diagnosis and intervention in newborn babies, and many countries have implemented a newborn screening (NBS) or pilot NBS program to detect SMN1 exon 7 deletions on dried blood spots. In the UK, there is no current NBS program for SMA, and no pilot studies have commenced. For consideration of adoption of NBS for a new condition, numerous criteria must be satisfied, including critical assessment of a working methodology. This study uses a commercially available real-time PCR assay to simultaneously detect two different DNA segments (SMN1 exon 7 and control gene RPP30) using DNA extracted from a dried blood spot. This study was carried out in a routine clinical laboratory to determine the specificity, sensitivity, and feasibility of SMA screening in a UK NBS lab setting. Just under 5000 normal DBSs were used alongside 43 known SMA positive DBSs. Study results demonstrate that NBS for SMA using real-time PCR is feasible within the current UK NBS Laboratory infrastructure using the proposed algorithm.